Knowledge, attitude, and practice toward COVID-19 among Iraqi people: a web-based cross-sectional study - Saad Ahmed Ali Jadoo; Adil Hassan Alhusseiny; Shukur Mahmood Yaseen; Mustafa Ali Mustafa Al-Samarrai; Ru’ya Abdulhadi Al-Rawi; Ahmed K. Al-Delaimy; Mohammed Waheeb Abed; Hanan Raheem Hassooni (Journal of Ideas in Health, 2020)
Background: Iraq was among the first countries invaded by the novel human coronavirus (SARS-COV-2) after China. This study aimed to assess the Iraqi people's knowledge, attitudes, and practices toward COVID-19 during the pandemic.